NREG: old banger or new vehicle for research?. Issue 1 (1st April 2010) - Rees, Colin; Rutter, Matthew
Abstract : The Northern Region Endoscopy Group (NREG) is a collaborative endoscopy network. NREG provides the opportunity for clinicians across the entire Northern region to undertake high quality, clinically meaningful, health service based research. NREG research is undertaken across a wide range of endoscopy units with pooling of resources and ideas. NREG has presented a large number of abstracts and is contributing to a number of National Institute for Health Research trials. NREG is collaborating with other research teams in the UK and a number of research grants have been secured. NREG aims to make a significant contribution to the field of endoscopic research over the coming years.